Influence of Service Quality and Hospital Image on Patient Loyalty with Patient Satisfaction - Mr. P. Pradeep; Dr. Jothi Jayakrishnan; Dr. Annamalai Solayappan; Dr. D. Sakthivel (Revista Electronica de Veterinaria, 2024)
Everyone has the dream of having a healthy body with which all the life activities can run effectively. Health is also a very important need for every individual because it is valuable and expensive. One of the efforts to improve health is to choose the health service facilities that are used. Salem SIMS hospital provided the Inpatient services are the main concern of hospital management because the number of inpatients is more than other treatments. The purpose of this study was to analyze the effect of service quality and hospital image through patient satisfaction on patient loyalty in Hospital services. This type of research is an associative study and the population in this study was all inpatients at Hospital in Salem city, Tamilnadu. The sampling method used is purposive sampling. Service Quality and hospital image have been taken as independent variables. Patient loyalty towards the hospital considered as dependent variable and patient satisfaction taken as intermediate variables. Path analysis has been used. The results showed that the quality of service, hospital image and satisfaction had a positive and significant effect on patient loyalty. Then service quality has a positive and significant effect on patient loyalty through hospital image. Hospital image has a positive and significant effect on patient loyalty.